CHARACTERISTICS OF BRICKS WITH RICE HUSK ASH FROM BRICK PRODUCTION WASTE - Irma Aswani Ahmad; Fildzah Atika; Ahmad Rifqi Asrib (Indonesian Journal of Multidisciplinary Science, 2022)
Concrete brick is one of the most widely used materials for walls. In fact, in the field, many bricks are damaged quickly, for example, broken or damp. This research aims to discover the process of making concrete brick using husk rice ash as additives and the difference in quality between ordinary brick and brick made from added rice husk ash. Adding rice husk ash is to utilize the husk waste, which is available in huge quantities. This research was conducted in a laboratory, using the analysis technique of compressive strength of the specimen and water absorption according to SNI 03-0349-1989. The results showed that adding rice husk ash percentage increased the absorption capacity of the bricks. Furthermore, the compressive strength of the bricks decreased with the addition of the percentage of rice husk ash. However, the compressive strength and absorption of the bricks with rice husk ash still meet the requirements SNI 03-0349-1989.